Islam Dan Sasaran Pendekatan - Agus Rifky Riduan; Hendriansyah; Pahila Sugiana; Suci Rahma Dini (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Studies and a researches on Islam are faced with a hope of how to give answer of the gap acruebetween theideality of the tachings of the religion on one side and the reality of life nd human understanding and rarional interptation which are more and move omproved of all things. A demand to “make” thetachings of religion “objective” becomes more and more strong. There for, an effort to formulate the relevan between what is essential to a religion and a becomes the dynamic of thoughts research on Islam, it is hoped that they can bridges the relevance of the teaching of the relegion to the needs of modernity of the era.